2016
DOI: 10.18203/2320-6012.ijrms20161960
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of patients with self-posioning with organphosphorous pesticides at a rural tertiary care hospital in Southern India

Abstract: Background: Organophosphate (OP) pesticides are the main agents for pest control in agricultural crops making them the agent of choice for self-poisoning. In India, self-poisoning with OP pesticides is the second most frequently reported method of suicide owing to its ready and easy availability with mortality varying from 12% to 50%. Methods: A retrospective study was conducted over a period of one year to compare the socio-demographic variables with the outcomes in patients with OP poisoning. A total 94 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The suicide mechanism with the highest prevalence index was poisoning with 66.5% [14]. In India, a research conducted by Falia [15] found that OP pesticides self-poisoning was the highest mechanism of suicide in rural areas as a result of to the lack of regulatory control over the same and the ease of availability of these compounds. Suicide attempts is a vital factor in determining the future rate of suicidal deaths as well as suicidal survivors; the survivors should undergo a psychiatric care as it has lower probability of subsequent [16].…”
Section: Introductionmentioning
confidence: 99%
“…The suicide mechanism with the highest prevalence index was poisoning with 66.5% [14]. In India, a research conducted by Falia [15] found that OP pesticides self-poisoning was the highest mechanism of suicide in rural areas as a result of to the lack of regulatory control over the same and the ease of availability of these compounds. Suicide attempts is a vital factor in determining the future rate of suicidal deaths as well as suicidal survivors; the survivors should undergo a psychiatric care as it has lower probability of subsequent [16].…”
Section: Introductionmentioning
confidence: 99%